2020
DOI: 10.1038/s41598-019-56906-w
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence of significant placental growth factor release by normal pregnancy placentas

Abstract: Placental growth factor (PlGF) is an angiogenic factor identified in the maternal circulation, and a key biomarker for the diagnosis and management of placental disorders. Furthermore, enhancing the PlGF pathway is regarded as a promising therapy for preeclampsia. The source of PlGF is still controversial with some believing it to be placental in origin while others refute this. To explore the source of PlGF, we undertook a prospective study enrolling normal pregnant women undergoing elective caesarean section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…It was reported that the available A placentomes was distributed among the fetus(es). Even if it was only one fetus, the feto-maternal units from both the ipsi-lateral and contra-lateral horn would serve the fetus (Cerdeira et al 2020). However, the functional demands on individual placentomes may vary and cause structural adjustments, as the number of fetuses increases.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the available A placentomes was distributed among the fetus(es). Even if it was only one fetus, the feto-maternal units from both the ipsi-lateral and contra-lateral horn would serve the fetus (Cerdeira et al 2020). However, the functional demands on individual placentomes may vary and cause structural adjustments, as the number of fetuses increases.…”
Section: Discussionmentioning
confidence: 99%
“…breech presentation). The uterine vein directly receives blood from the placenta, thus placentally-derived molecules are typically more abundant in these samples (Figure 3B) 32,33 . All three 5'-tRF were more abundant in uterine vein samples (median 1.4 fold, p<0.05 for all three) (Figure 3C).…”
Section: Plasma Ev 5'-trf Are Upregulated In Pregnancy and Placentall...mentioning
confidence: 99%